ANALISIS KEMAMPUAN PEMECAHAN MASALAH DENGAN HASIL BELAJAR ASPEK KOGNITIF SISWA PADA MATERI SISTEM PERSAMAAN LINEAR DUA VARIABEL (SPLDV) DI SMPS KARYAWAN TANJUNG MORAWA T.A.2024/2025 - Hutagaol, Diana Kristina; Naibaho, Tutiarny; Hutauruk, Agusmanto; Pangaribuan, Lena Rosdiana (Universitas Quality, 2024)
This study aims to determine the relationship and magnitude of the relationship between problem-solving ability and students' cognitive learning outcomes in the Two-Variable Linear Equation System (SPLDV) material in grade VIII of Tanjung Morawa Employee Junior High School T.A 2024/2025. The type of research used in this study is quantitative descriptive research and the instrument used is a descriptive test. The population in this study is all grade VIII students of Tanjung Morawa Employee Junior High School 2024/2025 consisting of 5 classes. By using cluster random sampling, a sample of students in grades VIII-1 was obtained. Data analysis uses a simple correlation coefficient and a determination coefficient. The results of the calculation were obtained which showed that there was a relationship between problem-solving ability and learning outcomes of students' cognitive aspects. The relationship between problem-solving ability and learning outcomes in the cognitive aspect of students is 50.5%. So it can be concluded that there is a significant relationship between problem-solving ability and learning outcomes of students' cognitive aspects in the material of the Two-Variable Linear Equation System (SPLDV) in grade VIII of SMPS Tanjung Morawa Employees T.A 2024/2025.”